Pengaruh Self Direct Learning Terhadap Prestasi Belajar Melalui Motivasi Belajar Pada Mata Pelajaran Ekonomi SMA Negeri 1 Singaparna - Fahiran, Muhammad Nodia Arza; Sadiah, Ati; Gumilar, Gugum (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The study aims to determine the effect of Self Direct Learning on Learning Achievement through Learning Motivation in Economics Subjects. The problem raised in this study is to examine and understand the extent to which Self-Directed Learning affects student learning achievement in Economics subjects, either directly or through learning motivation as a mediating variable. The research method used survey with descriptive design. The population is students of SMAN 1 Singaparna, a total of 181 people. The sampling technique used was proportionated random sampling, so that the sample taken was 125 students. Data collection techniques in this study used a questionnaire, and statistical tests using path analysis. The results showed that Self Direct Learning affects Learning Achievement directly, but does not affect indirectly through learning motivation.